SOP for water absorption capacity and cooking time in beans - Manzano, Kelly Tatiana; Soto Betancourt, Fabricio; Gallego Castillo, Sonia (2025)
This standard operating procedure (SOP) describes the stages involved in the process of estimating the water absorption capacity and cooking time of bean grain samples, using a Mattson Bean Cooker